2019
DOI: 10.3390/jcm8081165
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Blood Velocity and Flow in Early Diabetes and Diabetic Retinopathy Using Adaptive Optics Scanning Laser Ophthalmoscopy

Abstract: Using adaptive optics scanning laser ophthalmoscopy (AOSLO), we measured retinal blood velocity and flow in healthy control eyes and eyes of diabetic patients with or without retinopathy. This cross-sectional study included 39 eyes of 30 patients with diabetes (DM) with mild non-proliferative diabetic retinopathy (NPDR) or without retinopathy (DM no DR) and 21 eyes of 17 healthy age-matched controls. Participants were imaged with a commercial optical coherence tomography angiography (OCTA) device (RTVue-XR Ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 47 publications
0
51
1
Order By: Relevance
“…Other velocity measurements, such as those using targeted dye delivery, found vessels between 20 µm to 80 µm to exhibit power law exponents of 2.90, less than that predicted by Murray's law though larger than the values found here 21 . AOSLO measurements for larger vessels using a different technique also found an exponent closer to 3 43 . We do expect deviations from Murray's law for small vessels for a number of reasons.…”
Section: Discussionmentioning
confidence: 73%
“…Other velocity measurements, such as those using targeted dye delivery, found vessels between 20 µm to 80 µm to exhibit power law exponents of 2.90, less than that predicted by Murray's law though larger than the values found here 21 . AOSLO measurements for larger vessels using a different technique also found an exponent closer to 3 43 . We do expect deviations from Murray's law for small vessels for a number of reasons.…”
Section: Discussionmentioning
confidence: 73%
“…[19][20][21][81][82][83][84][85][86][87] Except for the biochemical changes, physiological changes also play a role in the process of DR. Hemodynamic dysfunction has been found in DR and may precede clinical DR. [88][89][90][91][92] Hemodynamic parameters, wall shear rate and wall shear stress are suggested reduced in the early stage of DR, as well as retinal blood velocity and ow, which could be markers of microvasculopathy. 88,93,94 Atherosclerosis has also been considered associated with the severity of DR, manifesting increased macrovascular artery intima-media wall thickness and accompanied by wider retinal vessel diameter in DR. [95][96][97] These studies emphasize the vital role of hemodynamic changes in the early stage of DR. CDDP in TCM theory is characterized by improving blood circulation (Pharmacopoeia of the People's Republic of China). The early application of CDDP in NPDR patients can signi cantly shorten the retinal circulation time and reduce capillary hemangioma, hard exudates, retinal hemorrhaging.…”
Section: Discussionmentioning
confidence: 99%
“…It is less well-established how retinal blood flow under resting conditions behaves in diabetes and DR. Evidence for both increased [44][45][46][47][48][49] and decreased retinal blood flow [50][51][52][53][54] have been reported in diabetes and early DR. A recent study suggested that the increased retinal blood flow is a consequence of early retinal hypoxia [49], which is associated with retinal vasodilatation [55,56].…”
Section: Ocular Vascular Changes In Diabetesmentioning
confidence: 99%